2018
DOI: 10.1111/ijfs.13964
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial potential of pomegranate peel: a review

Abstract: Pomegranate peel (PoP) is a byproduct of the fruit juice processing industry, comprising nearly 30-40% of fruit portion. PoP is rich in polyphenols (phenolic acids, tannins and flavonoids particularly anthocyanins) which are known to have diverse biological functions including effectiveness against pathogenic microorganisms. PoP has shown a broad spectrum antimicrobial activity (AMA) of PoP against both Gram-positive and Gram-negative bacteria. It also presented promising AMA against antibiotic resistant micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 47 publications
3
75
0
Order By: Relevance
“…Therefore, the extraction of antioxidants from PPW has drawn much attention among the scientific community (Singh & Saldaña, ; Wijngaard et al ., ; Alvarez et al ., ). Phenolic acids possessing antioxidative activity are recoverable from the PP waste and can be utilised for value addition in the processed foods (Singh et al ., ). Moreover, the utilisation of wastes as resources make environment greener and healthy.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the extraction of antioxidants from PPW has drawn much attention among the scientific community (Singh & Saldaña, ; Wijngaard et al ., ; Alvarez et al ., ). Phenolic acids possessing antioxidative activity are recoverable from the PP waste and can be utilised for value addition in the processed foods (Singh et al ., ). Moreover, the utilisation of wastes as resources make environment greener and healthy.…”
Section: Introductionmentioning
confidence: 97%
“…Šavikin et al reported that pomegranate peel exhibits high levels of free radical scavenging activities and strong antimicrobial activity due to its phenolic content [9]. Several studies reported the efficacy of extracts from pomegranate peel to inhibit both Gram-positive and Gram-negative bacterial growth such as foodborne pathogens, spoilage bacteria and human pathogens [10]. It was reported as well that pomegranate extracts display antifungal properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Starch-lipid complexes have some desirable functionalities in food systems. Singh and Byars [20] reported no occurrence of syneresis in yoghurt samples stored at 4 C when starch-lipid composites were used to replace milk solids in the production of low-fat yoghurts. Modification of maize and teff starches with stearic acid reduced the process of retrogradation in the resultant paste during cooling and storage.…”
Section: Introductionmentioning
confidence: 99%
“…[21] The enclosed lipid molecules in the form of amylose-lipid complexes, contribute to the stability of the amylose helix conformation by restricting the mobility of amylose [22,23] and thus prevents the amylose from getting involved in retrogradation. [20] Amylose-lipid complexes have been classified as part of the resistant starch fraction and do have similar health benefits as dietary fiber. [24,25] This is because complexes that are formed are less easily degraded by α-amylase enzymes.…”
Section: Introductionmentioning
confidence: 99%